1994
DOI: 10.1213/00000539-199407000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Phenylephrine Does Not Reduce Cerebral Perfusion During Canine Cardiopulmonary Bypass

Abstract: Gaseous microemboli during cardiopulmonary bypass (CPB) could injure the blood-brain barrier so that cerebral vasoconstriction would result from infusing alpha-agonist drugs, such as phenylephrine. Cerebral blood flow (radioactive microspheres) and metabolism were measured in seven dogs after rewarming from 150 min hypothermic CPB with bubble oxygenators used to produce gaseous microemboli. Phenylephrine (40 micrograms/min) was infused directly into the brachiocephalic artery so that aortic pressure before (80… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 16 publications
2
17
0
Order By: Relevance
“…We agree with Grocott that a 1-2% decrease in rSO 2 is small and will probably not directly lead to worsened clinical outcome. However, the finding that phenylephrine causes a reduction in rSO 2 confirms earlier work in awake [2,3] and anaesthetised patients [4], as well as studies in patients during bypass [5]. Indeed, to the best of our knowledge, no study exists that shows an increase in rSO 2 after phenylephrine administration.…”
supporting
confidence: 85%
See 1 more Smart Citation
“…We agree with Grocott that a 1-2% decrease in rSO 2 is small and will probably not directly lead to worsened clinical outcome. However, the finding that phenylephrine causes a reduction in rSO 2 confirms earlier work in awake [2,3] and anaesthetised patients [4], as well as studies in patients during bypass [5]. Indeed, to the best of our knowledge, no study exists that shows an increase in rSO 2 after phenylephrine administration.…”
supporting
confidence: 85%
“…Whereas they suggest that this is a direct effect on the cerebral vasculature, with cerebral vasoconstriction reducing cerebral blood flow (CBF) and thus rSO 2 , their selective citing of the literature supporting a vasoconstrictive effect [3,4] fails to address other wellconducted studies that showed no effect of phenylephrine on CBF [5]. Indeed, a vasoconstrictive effect on rSO 2 is far more likely a manifestation of the inherent extracranial contamination that variably occurs with cerebral oximeters, particularly the one that they used in their study (INVOS 5100 cerebral oximeter; Somanetics Company, Troy, MI, USA) [6].…”
mentioning
confidence: 99%
“…Previous studies have shown that intra-arterial phenylephrine (␣ 1 -adrenoreceptor agonist) does not cause any relevant MCA vasoconstriction. 25,26 Likewise, nitroprusside administered during craniotomy in humans did not affect MCA vessel diameter. 27 Therefore, it seems reasonable to assume that changes in MCAv measured via transcranial Doppler ultrasound were proportional to changes in CBF.…”
Section: Methodological Considerationsmentioning
confidence: 92%
“…It is possible that infusion of the vasoactive drugs had a direct effect on the diameter of the MCA. However, previous studies have demonstrated that intra-arterial infusion of nitroprusside or phenylephrine does not cause any relevant change in MCA diameter (9,15). It has been suggested that the integrity of the blood-brain barrier eliminates a possible influence of these drugs on cerebral vessels of different sizes (9,15).…”
Section: Methodological Considerationsmentioning
confidence: 99%